Research on Multipass Hot Spinning Process Technology of AZ80 Magnesium Alloy Shell. (30th November 2019) - Liang, Wei; Guan, Lin; Lv, Qiongying; Xing, Zhigang
Abstract : Combined with finite element numerical simulation analysis, the hot-spin forming technology of cylindrical AZ80 magnesium alloy parts was studied in the paper. The multipass hot-spin forming of magnesium alloy shell parts was simulated by the ABAQUS software to analyze the stress and strain distribution and change during spinning for the preliminary test process parameters in the magnesium alloy spinning test. Then, the process parameters were optimized during the hot spinning test, especially the matching relationship between temperature parameter and thinning rate parameter, and the hot spinning magnesium alloy shell parts with the expected technical specifications were finished.